Safety and Pharmacokinetics of Intravaginal Rings Delivering Tenofovir in Pig-Tailed Macaques - Moss, John A. (American Society for Microbiology, 2012)
Antiretroviral-based microbicides applied topically to the vagina may play an important role in protecting women from HIV infection. Incorporation of the nucleoside reverse transcriptase inhibitor tenofovir (TFV) into intravaginal rings (IVRs) for sustained mucosal delivery may lead to increased microbicide product adherence and efficacy compared with those of conventional vaginal formulations. Formulations of a novel “pod IVR” platform spanning a range of IVR drug loadings and daily release rates of TFV were evaluated in a pig-tailed macaque model. The rings were safe and exhibited sustained release at controlled rates over 28 days. Vaginal secretion TFV levels were independent of IVR drug loading and were able to be varied over 1.5 log units by changing the ring configuration. Mean TFV levels in vaginal secretions were 72.4 ± 109 μg ml(−1) (slow releasing) and 1.84 ± 1.97 mg ml(−1) (fast releasing). The mean TFV vaginal tissue concentration from the slow-releasing IVRs was 76.4 ± 54.8 μg g(−1) and remained at steady state 7 days after IVR removal, consistent with the long intracellular half-life of TFV. Intracellular tenofovir diphosphate (TFV-DP), the active moiety in defining efficacy, was measured in vaginal lymphocytes collected in the study using the fast-releasing IVR formulation. Mean intracellular TFV-DP levels of 446 ± 150 fmol/10(6) cells fall within a range that may be protective of simian-human immunodeficiency virus strain SF162p3 (SHIV(SF162p3)) infection in nonhuman primates. These data suggest that TFV-releasing IVRs based on the pod design have potential for the prevention of transmission of human immunodeficiency virus type 1 (HIV-1) and merit further clinical investigation.